What's Wrong with the Arts Is What's Wrong with Society - Scitovsky, Tibor (American Economic Review, 2016)
this country. Measured by admissions to live performances of legitimate theater and music, our art consumption per head is less than a half of West Germany's and Austria's, little better than a half of Norway's and Switzerland's, and less than a third of such East European countries as Hungary, Czechoslovakia and East Germany. In a cultural center like San Francisco, the past season's more than 1.8 million admissions are very impressive when related to her 700,000 populationthey probably exceed those in any city of comparable size anywhere in the world. But when one remembers our suburban way of life and the fact that San Francisco is the downtown of 4' million Bay Area residents, then this turns out to be not quite so high a figure, more in keeping with our low national average. The American national average used in these comparisons is very approximate and subject